2020
DOI: 10.1002/lary.28983
|View full text |Cite
|
Sign up to set email alerts
|

Metastatic Patterns and Prognosis of de novo Metastatic Nasopharyngeal Carcinoma in the United States

Abstract: Objective: To evaluate the distant metastatic patterns and prognostic factors for overall survival (OS) and cancer-specific survival (CSS) in de novo metastatic nasopharyngeal carcinoma (mNPC) using the Surveillance, Epidemiology, and End Results (SEER) database. Methods: Patients with de novo mNPC who had been diagnosed between 2004 and 2016 were identified from the SEER database. Kaplan-Meier analysis was used to calculate OS and CSS. Log-rank tests were employed to measure survival variation among subgroups… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 37 publications
1
7
2
Order By: Relevance
“…Chemotherapy at the IVC stage improved OS (HR: 0.40, 95% CI: 0.25–0.65, and p < 0.001) but did not significantly affect CSS. Furthermore, chemotherapy was significantly associated with improved OS in this study, which is consistent with other studies, which reported that chemotherapy may improve the OS of older patients with de novo metastatic NPC 16 , 29 . Unfortunately, radiation was not found to be an independent prognostic factor and only improved OS.…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…Chemotherapy at the IVC stage improved OS (HR: 0.40, 95% CI: 0.25–0.65, and p < 0.001) but did not significantly affect CSS. Furthermore, chemotherapy was significantly associated with improved OS in this study, which is consistent with other studies, which reported that chemotherapy may improve the OS of older patients with de novo metastatic NPC 16 , 29 . Unfortunately, radiation was not found to be an independent prognostic factor and only improved OS.…”
Section: Resultssupporting
confidence: 92%
“…The paper reported that single organ metastasis had a better prognosis than multiple organ metastasis 27 . Contrary to this finding, the number of organs with metastasis did not affect the prognosis, but the number of metastatic lesions did, and patients with multiple lesions had a worse prognosis than those with single lesions 16 , 19 , 30 . In our study, patients with single organ metastasis did not have better survival, which may be because they may exhibit more metastases within the organ.…”
Section: Resultscontrasting
confidence: 86%
See 2 more Smart Citations
“…In recent years, the patterns of DM as prognostic indicators in de novo stage IV metastatic cancers have been investigated increasingly, which provided additional information for clinical practice [16] , [17] , [18] . However, the progression of understanding the epidemiology of primary metastatic ES is limited.…”
Section: Introductionmentioning
confidence: 99%